From waste COVID-19 face masks to fuel: Pyrolysis-oil/diesel blends with hydrogen enrichment in a CI engine - Agbulut, Umit; Polat, Fikret; Karagoz, Mustafa; Saridemir, Suat; Abanoz, Beyzanur Yavuz; Vozka, Petr (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
The widespread use of face masks was crucial during the COVID-19 pandemic, but their improper disposal creates significant environmental problems. This study explores a sustainable solution by converting waste masks into an energy source through pyrolysis. The liquid product is blended with diesel at 30 % (Mask 30) and tested in a three-cylinder diesel engine under loads of 15-60 Nm at 2000 rpm. To counteract deterioration in engine characteristics, hydrogen is introduced at flow rates of 10, 20, and 30 L/min, resulting in fuel variants Mask 30 + 10 L/min H2, Mask 30 + 20 L/min H2, and Mask 30 + 30 L/min H2. The BSFC of Mask 30 increases by 8.08 % compared to diesel fuel, while BTE decreases. With hydrogen, BSFC decreases by 8.66 %, 15.93 %, and 24.99 % compared to Mask 30, and emissions also decrease. This study demonstrates that COVID-19 masks can be diverted from the environment via pyrolysis and evaluated as an alternative fuel.
Keywords: COVID-19 masks; Waste-to-energy; Engine behaviours; Combustion; Emission; DIESEL-ENGINE; DUAL FUEL; EXHAUST EMISSIONS; PERFORMANCE; Chemistry; Electrochemistry; Energy & Fuels